2016
DOI: 10.1111/ane.12634
|View full text |Cite
|
Sign up to set email alerts
|

Addition of sodium criterion to SOAR stroke score

Abstract: The SOAR-Na did not perform considerably better than the SOAR stroke score. However, the performance of SOAR-Na in those with CKD and dysglycaemias requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…For predicting length of hospital stay, dichotomized at seven days, AUROC was 0.61 (95%CI: 0.60–0.62). Although external validation was not included as part of the derivation paper, SOAR has been subsequently assessed in independent datasets in five studies (98103). Four studies assessed the scale's performance for predicting early mortality (inpatient, 7-day, discharge, and 90-day).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For predicting length of hospital stay, dichotomized at seven days, AUROC was 0.61 (95%CI: 0.60–0.62). Although external validation was not included as part of the derivation paper, SOAR has been subsequently assessed in independent datasets in five studies (98103). Four studies assessed the scale's performance for predicting early mortality (inpatient, 7-day, discharge, and 90-day).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, the finding was confirmed in an independent Chinese patient sample: AUROC of 0.78 (95%CI: 0.76–0.81) and 0.79 (95%CI: 0.77–0.80) for discharge and 90-day mortality, respectively, compared to 0.72 (95%CI: 0.70–0.75) and 0.70 (95%CI: 0.69–0.72), respectively, with higher estimates reported for mSOAR. The remaining two updates of SOAR included adding admission blood glucose levels (SOAR-G) and admission sodium (SOAR-Na) (101, 103). Both concluded that the original and revised scales performed well, however without evidence of the latter offering a significant improvement in discriminatory power.…”
Section: Resultsmentioning
confidence: 99%
“…F) Further adjusted for the acute illness parameters of the admission serum sodium, albumin, and glucose. 15 16 17 …”
Section: Mehtodsmentioning
confidence: 99%